Simulasi Prinsip Iron Dome Berbasis Matlab Pada Materi Kinematika Gerak - Kumala, Siti Ayu; Nurhadi, Nurhadi; Jahrudin, Ahmad; Huda, Didik Nur (Navigation Physics : Journal of Physics Education, 2024)
Iron Dome is a defense system used in wars between countries. This defense system became very popular during Israel's invasion of Gaza in 2023, even though this technology was introduced by Israel in 2011. The concept of the Iron Dome defense system is to prevent enemy missiles from entering the defense area by launching missiles at the enemy missiles. so that at a certain distance the missile is destroyed before it reaches the area. This principle is very interesting as a way of learning physics that is contextual to life. The aim of this research is to simulate the motion of missiles and missiles using the Iron Dome working principle based on the MATLAB GUI. This research method consists of several stages, namely literature study, creating a Graphic User Interface for the MATLAB display, coding to run the GUI, and testing the running of the MATLAB program that has been created. The results obtained are a MATLAB-based program or application for simulating Iron Dome principles. By creating the Iron Dome simulation, students become more interested and understand the concept of motion kinematics more easily because it is very contextual to life.